Complexity of major UK companies between 2006 and 2010: Hierarchical structure method approach - Deviren, Bayram; Doenmez, Cem Cagri; Kantar, Ersin; Keski̇n, Mustafa; Ulusoy, Tolga; Shirvani, Ayoub (Elsevier BV, 2012)
Abstract This study reports on topology of the top 40 UK companies that have been analysed for predictive verification of markets for the period 2006–2010, applying the concept of minimal spanning tree and hierarchical tree (HT) analysis. Construction of the minimal spanning tree (MST) and the hierarchical tree (HT) is confined to a brief description of the methodology and a definition of the correlation function between a pair of companies based on the London Stock Exchange (LSE) index in order to quantify synchronization between the companies. A derivation of hierarchical organization and the construction of minimal-spanning and hierarchical trees for the 2006–2008 and 2008–2010 periods have been used and the results validate the predictive verification of applied semantics. The trees are known as useful tools to perceive and detect the global structure, taxonomy and hierarchy in financial data. From these trees, two different clusters of companies in 2006 were detected. They also show three clusters in 2008 and two between 2008 and 2010, according to their proximity. The clusters match each other as regards their common production activities or their strong interrelationship. The key companies are generally given by major economic activities as expected. This work gives a comparative approach between MST and HT methods from statistical physics and information theory with analysis of financial markets that may give new valuable and useful information of the financial market dynamics.
Keywords: 8. Economic growth